A composite positive electrode material and its preparation method and application

By using Co-molecular ferroelectric crystals to carry out inhomogeneous island-like coating on the surface of the positive electrode material of the solid-state lithium battery, the problems of large impedance of the space charge layer and poor interface stability of the positive electrode electrolyte interface are solved, and the high coulombic efficiency, rate performance and cycling performance of the battery are improved.

CN119092696BActive Publication Date: 2025-03-18WEICHAI POWER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411562884.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-18
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The prior art is difficult to solve the problems of large impedance of the space charge layer at the interface of the positive electrode electrolyte in solid-state lithium batteries, resulting in poor battery circulation performance.

Method used

The Co-containing molecule-containing ferroelectric crystal is used to coat the Co-rich layer on the surface of the positive electrode material in an inhomogeneous island-like manner, suppress the charge transfer impedance of the space charge layer, and stabilize the positive electrode electrolyte interface through the Co-rich layer to reduce interface side reactions and structural damage.

Benefits of technology

The transmission efficiency of Li ions at the interface between the positive electrode and the electrolyte in a solid-state battery is improved, the Coulomb efficiency and rate performance of the battery are improved, and the cycle performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119092696B_ABST
    Figure CN119092696B_ABST
Patent Text Reader

Abstract

The present invention provides a composite positive electrode material and a preparation method and application thereof, belonging to the technical field of battery materials. The composite positive electrode material is a core-shell structure, the core is a positive electrode material, the shell is a Co-rich layer, and the outer surface of the Co-rich layer is coated with Co-containing molecular ferroelectric crystals in an island shape. The present invention uses Co-containing molecular ferroelectric crystals to non-uniformly coat the Co-rich layer on the surface of the positive electrode material in an island shape. On the one hand, the charge transfer impedance caused by the space charge layer is suppressed by the Co-containing molecular ferroelectric crystals, thereby improving the transmission efficiency of Li ions at the interface between the positive electrode and the electrolyte in the solid-state battery, thereby improving the coulombic efficiency and rate performance of the battery. On the other hand, the Co-rich layer on the surface of the positive electrode material can stabilize the positive electrode electrolyte interface, eliminate the negative effects caused by the interface side reactions, element dissolution, contact failure and positive electrode cracks at the positive electrode electrolyte interface, and improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a composite positive electrode material and a preparation method and application thereof. Background Art

[0002] Some crystals have spontaneous polarization within a certain temperature range, and the direction of their spontaneous polarization is turned due to the turning of the external electric field. This property of the crystal is called ferroelectricity, and the crystal with ferroelectricity is called a ferroelectric crystal. The existing patent CN117457861A discloses the use of molecular ferroelectrics coated on the surface of the positive electrode to improve the high impedance caused by the space charge layer between the positive electrode and the electrolyte of the solid-state lithium battery, thereby improving the coulomb efficiency and rate performance of the battery. In this patent, after the molecular ferroelectric crystal is coated with the positive electrode material, a reverse ferroelectric built-in electric field is constructed at the positive electrode / electrolyte interface, thereby opening a fast transmission channel for Li ions in the space charge layer. As a physical barrier layer, molecular ferroelectrics can effectively prevent adverse chemical reactions at the interface between the positive electrode and the electrolyte when uniformly coated, and reduce structural damage and by-product generation at the positive electrode / electrolyte interface. However, molecular ferroelectrics are often poor Li ion conductors, and completely coating the surface of the positive electrode will greatly affect the transmission of Li ions. Therefore, when using molecular ferroelectrics to coat the positive electrode, uniform coating is often avoided, and non-uniform island coating is pursued instead, which is different from the common coating process. Non-uniform coating means that part of the positive electrode surface is in direct contact with the electrolyte. In this patent, the solid-state battery uses a sulfide electrolyte as a Li ion conductor, and direct contact between the sulfide electrolyte and the positive electrode often causes (electro)chemical side reactions, resulting in an increase in interfacial impedance and a decline in positive electrode performance, which is not conducive to battery performance. Therefore, this patent uses LiCoO, which is relatively stable to sulfide electrolytes. 2 As the positive electrode material, LiCoO 2 The specific capacity is 120mAh / g, which is comparable to the common ternary cathode material Li(Ni x Co y Mn z ) 2 Compared with (x+y+z=1), the specific capacity is lower, which is not conducive to improving the energy density of solid-state batteries. 2 The interface with the sulfide electrolyte is still not completely stable, and the instability will still cause the battery cycle performance to decline. Therefore, although this patent solves the problem of large space charge layer impedance at the positive electrode electrolyte interface to a certain extent, it cannot solve the problem of positive electrode electrolyte interface stability, and the solid-state battery cycle performance is poor.

[0003] In summary, how to solve both the problem of large space charge layer impedance at the positive electrode electrolyte interface and the problem of positive electrode electrolyte interface stability, thereby significantly improving the cycle performance of solid-state batteries, is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a composite positive electrode material and a preparation method and application thereof. The present invention uses Co-containing molecular ferroelectric crystals to perform non-uniform island coating on the Co-rich layer on the surface of the positive electrode material. On the one hand, the charge transfer impedance caused by the space charge layer is suppressed by the Co-containing molecular ferroelectric crystals, thereby improving the transmission efficiency of Li ions at the interface between the positive electrode and the electrolyte in the solid-state battery, thereby improving the coulombic efficiency and rate performance of the battery. On the other hand, the Co-rich layer on the surface of the positive electrode material can stabilize the positive electrode electrolyte interface, eliminate the negative effects caused by the interface side reactions, element dissolution, contact failure and positive electrode cracks at the positive electrode electrolyte interface, and improve the cycle performance of the battery.

[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a composite positive electrode material, wherein the composite positive electrode material is a core-shell structure, wherein the core is a positive electrode material, the shell is a Co-rich layer, and the outer surface of the Co-rich layer is coated with Co-containing molecular ferroelectric crystals in an island shape;

[0007] The positive electrode material is a ternary positive electrode material, and the general chemical formula is Li(Ni x Co y Mn z ) 2 , where, x+y+z=1, 0<x<1, 0<y<1, 0<z<1.

[0008] It should be noted that when the positive electrode and electrolyte surfaces are in contact, the uneven electrochemical potential on both sides of the interface causes Li ions to spontaneously migrate from the electrolyte side to the positive electrode side. The Li ions on the electrolyte side continue to decrease, eventually resulting in the formation of a Li ion depletion zone on the electrolyte side, namely the space charge layer. The built-in electric field E formed by it seriously hinders the transmission of Li ions from the positive electrode to the electrolyte, affecting the coulombic efficiency and rate performance of the battery. In order to solve the instability of the positive electrode electrolyte interface and the impedance effect of the space charge layer, in the existing positive electrode coating modification process, Li ion conductive electron insulating oxides (such as LiNbO 3 or Li 2 ZrO 3 ) as a coating material, an interface physical barrier is constructed on the basis of alleviating the space charge layer, which alleviates the interface instability problem to a certain extent. However, these oxides often use relatively expensive organic niobium sources or zirconium sources to participate in the reaction in the coating process, and the coating process is relatively complicated, requiring the formation of a completely uniform, thin and dense coating layer, and the process indicators are relatively high.

[0009] To this end, the present application utilizes Co-containing molecular ferroelectric crystals to perform non-uniform island coating of the Co-rich layer on the surface of the positive electrode material, which not only avoids the formation of a completely uniform coating layer, but also has relatively low process index requirements and a relatively simple process; and, with the help of Co-containing molecular ferroelectric crystals, the charge transfer impedance caused by the space charge layer is suppressed, thereby improving the transmission efficiency of Li ions at the interface between the positive electrode and the electrolyte in the solid-state battery, thereby improving the coulombic efficiency and rate performance of the battery. At the same time, the Co-rich layer on the surface of the positive electrode material can stabilize the positive electrode electrolyte interface, eliminate the negative effects caused by interfacial side reactions, element dissolution, contact failure and positive electrode cracks at the positive electrode electrolyte interface, and improve the cycle performance of the battery.

[0010] It should be noted that the positive electrode material provides Li ions when charging in a solid-state battery, migrates to the negative electrode through the electrolyte, and provides the charging capacity of the battery; the solid electrolyte (SE) provides a transmission channel for Li ions in a solid-state battery, transporting Li ions from the positive electrode to the negative electrode during charging, and transporting Li ions from the negative electrode back to the positive electrode during discharge. The space charge layer refers to: when the positive electrode and the electrolyte come into contact with the interface, the Li ions driven by the Li ion concentration difference often move from the electrolyte layer to the positive electrode side to balance the difference in electrochemical potential of the Li ions on both sides of the interface to achieve thermodynamic equilibrium; the electrochemical potential is strongly related to the concentration of Li ions in each system, so the electrochemical potential of SE is higher than that of the positive electrode; because the positive electrode material is often a mixed ion-electron conductor, it means that the positive electrode can provide electrons to neutralize the Li ions enriched on the positive electrode side, causing the Li ions in the electrolyte to continue to move toward the positive electrode, and eventually leading to the formation of a Li ion depletion zone on the SE side of the interface, namely the space charge layer; the space charge layer is not conducive to the transport of Li ions in the battery, and will form a large charge transfer impedance; the charge transfer impedance is manifested as the adsorption capacity of the positive electrode electrolyte interface for Li ions, and the ability of charge transfer to cause Li ions to undergo redox reactions at the interface.

[0011] Preferably, the Co-containing molecular ferroelectric crystal is a Co-containing organic-inorganic hybrid molecular ferroelectric.

[0012] Preferably, the Co-containing organic-inorganic hybrid molecular ferroelectric comprises C 10 N 2 H 21 Bc 3 , C 10 N 2 H 21 CoCl 3 , C 10 N 2 H 21 CoI 3 , [C 5 H 12 N] 2 Bc4 , [C 5 H 12 N] 2 CoCl 4 , [C 5 H 12 N] 2 CoI 4 、[(CH 3 ) 3 NCH 2 Cl]CoCl 4 、[(CH 3 ) 3 NCH 2 Br]CoBr 4 or [(CH 3 ) 3 NCH 2 I]CoI 4 Any one or a combination of at least two of the following.

[0013] Preferably, based on the mass of the inner core, the mass content of the Co-containing molecular ferroelectric crystal is 0.1-5%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%.

[0014] In the present invention, if the mass content of the Co-containing molecular ferroelectric crystal is too little, it is not conducive to constructing a Li ion fast transmission channel in the space charge layer, and the rate performance is poor; if the mass content of the Co-containing molecular ferroelectric crystal is too high, it is not conducive to the Li ion transmission at the positive electrode electrolyte interface, and the molecular ferroelectric coating layer forms a physical barrier with excessive impedance, which hinders the Li ion transmission.

[0015] Preferably, the Co-rich layer has a thickness of 1-10 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.

[0016] In the present invention, if the thickness of the Co-rich layer is too small, an effective cathode electrolyte stable interface cannot be formed, and the interface side reaction is serious; if the thickness of the Co-rich layer is too large, the transmission of Li ions at the cathode electrolyte interface is affected, and the charge transfer impedance is too large.

[0017] Preferably, in the Co-rich layer, the mass content of the Co element is ≥15%, for example, it may be 15%, 20%, 40%, 50% or 60%.

[0018] It should be noted that the material of the Co-rich layer can be a ternary positive electrode Li (Ni x Co y Mn z ) 2Combination with a solid solution containing Co halide, etc.

[0019] In a second aspect, the present invention provides a method for preparing the composite positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0020] (1) The positive electrode material and the Co-containing halide are mixed for liquid phase coating, and then sintered to obtain a positive electrode material with a Co-containing layer coated on the surface.

[0021] (2) The positive electrode material coated with the Co layer and the N-containing organic matter are mixed to carry out an in-situ reaction, and then sintered after the reaction is completed to obtain the composite positive electrode material.

[0022] In the preparation method provided by the present invention, the unreacted Co-containing halide on the surface of the Co-rich layer is used to react in situ to achieve island-shaped coating of Co-containing molecular ferroelectric crystals. This strategy makes the bonding strength between the Co-containing molecular ferroelectric crystals and the positive electrode surface higher. During the battery cycle, the coating layer is less likely to fall off, and the corresponding cycle life performance is further improved.

[0023] Preferably, the Co-containing halide in step (1) comprises a divalent Co-containing halide and / or a trivalent Co-containing halide.

[0024] Preferably, the divalent Co-containing halide comprises CoF 2 、CoCl 2 ,CoBr 2 or CoI 2 Any one or a combination of at least two of the following.

[0025] Preferably, the trivalent Co-containing halide comprises CoF 3 and / or CoCl 3 .

[0026] Preferably, the mass of the Co-containing halide accounts for 0.5-1.5wt% of the mass of the positive electrode material, for example, it can be 0.5wt%, 0.7wt%, 1wt%, 1.2wt% or 1.5wt%.

[0027] Preferably, the sintering temperature in step (1) is 600-800°C, for example, 600°C, 650°C, 700°C, 750°C or 800°C, and the constant temperature time is 4-8h, for example, 4h, 5h, 6h, 7h or 8h.

[0028] In the present invention, if the sintering temperature is too low, a Co-rich layer solid solution tightly bonded to the surface of the positive electrode material cannot be formed; if the sintering temperature is too high, the positive electrode material will be destroyed, the positive electrode material will be thermally decomposed, and the structure will collapse.

[0029] Preferably, the sintering treatment in step (1) is carried out in an oxygen atmosphere.

[0030] Preferably, the N-containing organic matter in step (2) has a spherical or spherical structure.

[0031] In the present invention, the N-containing organic matter with a spherical or spherical structure can easily undergo a disordered to ordered structural phase transition from high temperature to low temperature, and is suitable for designing phase-change molecular ferroelectric materials.

[0032] Preferably, the N-containing organic matter in step (2) includes N-containing heterocyclic organic matter and / or trimethylethylchloroamine.

[0033] In the present invention, the N atom in the N-containing heterocyclic organic compound can increase the electron cloud density of the carbon atom on the ring and activate the ring to undergo electrophilic substitution reactions such as halogenation reactions, such as reacting with Co-containing halides to generate Co-containing molecular ferroelectrics.

[0034] Preferably, the N-containing heterocyclic organic compound includes a five-membered N-containing heterocyclic organic compound and / or a six-membered N-containing heterocyclic organic compound.

[0035] It should be noted that the five-membered N-containing heterocyclic organic compound may be a N-containing heterocyclic ring such as pyrrole and azole, and the six-membered N-containing heterocyclic organic compound may be a N-containing heterocyclic ring such as oxazine, pyridine, phenoxyl, etc. Exemplary examples include quinuclidine, triethylenediamine (DBACO), cyclopentylamine and its derivatives.

[0036] Preferably, the N-containing heterocyclic organic compound includes bromobutyltriethylenediethylamine.

[0037] Preferably, the mass of the N-containing organic matter in step (2) accounts for 0.2-2.5wt% of the mass of the positive electrode material coated with the Co-containing layer on the surface, for example, it can be 0.2wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt% or 2.5wt%.

[0038] Preferably, the temperature of the in-situ reaction in step (2) is 50-70°C, for example, 50°C, 60°C or 70°C, etc., and the constant temperature time is 1-3h, for example, 1h, 2h or 3h, etc.

[0039] In the present invention, if the temperature of the in-situ reaction is too low, the molecular ferroelectric cannot be synthesized; if the temperature of the in-situ reaction is too high, the synthesis purity of the molecular ferroelectric is poor.

[0040] Preferably, the sintering temperature in step (2) is 100-300°C, for example, 100°C, 150°C, 200°C, 250°C or 300°C, and the constant temperature time is 3-5h, for example, 3h, 4h or 5h.

[0041] In the present invention, if the sintering temperature in step (2) is too low, the bonding strength between the synthesized molecular ferroelectric and the positive electrode is poor, and the molecular ferroelectric falls off from the positive electrode due to stress accumulation during the subsequent battery positive electrode cycle process; if the sintering temperature in step (2) is too high, the molecular ferroelectric is destroyed and decomposed.

[0042] Preferably, the sintering in step (2) is carried out in an oxygen atmosphere.

[0043] Preferably, the preparation method comprises the following steps:

[0044] (1) stirring and mixing a Co-containing halide and a solvent (such as water), then adding a positive electrode material and stirring for 1-3 hours (such as 1 hour, 2 hours or 3 hours) to obtain a suspension, then drying at a temperature of 60-100°C (such as 60°C, 70°C, 80°C, 90°C or 100°C) to obtain a positive electrode material coated with a Co-containing halide, and then sintering the Co-containing halide-coated positive electrode material in an oxygen atmosphere to obtain a positive electrode material having a surface coated with a Co-containing layer, wherein the outer surface of the Co-containing layer contains unreacted Co-containing halide;

[0045] The sintering temperature is 600-800°C and the constant temperature time is 4-8h.

[0046] (2) Stirring and mixing the N-containing organic matter and the solvent (such as water), then adding the positive electrode material with the surface coated with the Co-containing layer, and carrying out an in-situ reaction at a temperature of 50-70°C for 1-3 hours to obtain a positive electrode material with a Co-rich layer surface in-situ generated with Co molecular ferroelectrics, and then sintering the positive electrode material in an oxygen atmosphere at a sintering temperature of 100-300°C for a constant temperature time of 3-5 hours to obtain the composite positive electrode material.

[0047] In a third aspect, the present invention provides a solid-state battery, wherein the positive electrode plate of the solid-state battery includes the composite positive electrode material as described in the first aspect, or includes the composite positive electrode material prepared by the preparation method as described in the second aspect.

[0048] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) The present invention utilizes Co-containing molecular ferroelectric crystals to perform non-uniform island coating on the Co-rich layer on the surface of the positive electrode material. On the one hand, the Co-containing molecular ferroelectric crystals suppress the charge transfer impedance caused by the space charge layer, thereby improving the transmission efficiency of Li ions at the interface between the positive electrode and the electrolyte in the solid-state battery, thereby improving the coulombic efficiency and rate performance of the battery. On the other hand, the Co-rich layer on the surface of the positive electrode material can stabilize the positive electrode electrolyte interface, eliminate the negative effects caused by the interface side reactions, element dissolution, contact failure and positive electrode cracks at the positive electrode electrolyte interface, and improve the cycle performance of the battery.

[0051] (2) In the preparation method provided by the present invention, the unreacted Co-containing halide on the surface of the Co-rich layer is used to react in situ to achieve island-like coating of the Co-containing molecular ferroelectric crystals. This strategy makes the bonding strength between the Co-containing molecular ferroelectric crystals and the positive electrode surface higher. During the battery cycle, the coating layer is less likely to fall off, and the corresponding cycle life performance is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a schematic diagram of the structure of the composite positive electrode material provided in Example 1 of the present invention.

[0053] Figure 2 The present invention uses Co-containing ferroelectric crystals to construct Li + Mechanistic diagram of the transmission channel.

[0054] Among them, 1-positive electrode material; 2-Co-rich layer; 3-ferroelectric crystal containing Co molecules. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1

[0057] This embodiment provides a composite positive electrode material, such as Figure 1 As shown, the composite positive electrode material is a core-shell structure, the core is the positive electrode material 1, the shell is the Co-rich layer 2, and the outer surface of the Co-rich layer 2 is coated with Co-containing molecular ferroelectric crystals 3 in an island shape;

[0058] The positive electrode material 1 is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ;

[0059] The Co-containing molecular ferroelectric crystal 3 is C 10 N 2 H21 Bc 3 , based on the mass of the core, the mass content of the Co-containing ferroelectric crystal 3 is 1%;

[0060] The thickness of the Co-rich layer 2 is 5 nm, the mass content of Co atoms in the Co-rich layer 2 is 19.4%, and the material of the Co-rich layer 2 is LiNi 0.8 Co 0.1 Mn 0.1 O 2 With CoBr 2 Solid solution, abbreviated as LiNi 0.8 Co 0.6 Mn 0.1 O 2 -1.5Co 0.5 Br 2 Solid solution.

[0061] This embodiment also provides a method for preparing the composite positive electrode material, the preparation method comprising the following steps:

[0062] (1) At 20°C, 10 mmol of 1 wt% positive electrode CoBr 2 Add to 20 mL of distilled water and stir until dissolved, then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The powder was stirred at 600 rpm for 2 h using a magnetic stirrer to obtain a uniform suspension, which was then heated and evaporated at 80 °C to obtain CoBr 2 The coated cathode material is then heated in an oxygen atmosphere to 2 The coated positive electrode material is sintered to obtain a positive electrode material with a surface coated with a Co-rich layer, wherein the outer surface of the Co-rich layer contains unreacted CoBr 2 ;

[0063] The sintering temperature is 700°C and the constant temperature time is 6h.

[0064] (2) At 20°C, 20 mmol of bromobutyltriethylenediethylamine ([CH 3 (CH 2 ) 3 -Dabco] + ·Br - ) (accounting for 2.27wt% of the mass of the positive electrode material coated with the Co layer on the surface) was added into 20mL of distilled water and stirred until dissolved, and then the positive electrode material coated with the Co layer on the surface was added, and stirred at 600rpm for 2h using a magnetic stirrer at a temperature of 60°C to perform an in-situ reaction, and the in-situ generated C on the surface of the Co-rich layer was obtained after filtration.10 N 2 H 21 Bc 3 The positive electrode material is then sintered in an oxygen atmosphere at a temperature of 300° C. for a constant temperature time of 4 hours to obtain the composite positive electrode material.

[0065] Example 2

[0066] This embodiment provides a composite positive electrode material, wherein the composite positive electrode material is a core-shell structure, wherein the core is a positive electrode material, the shell is a Co-rich layer, and the outer surface of the Co-rich layer is coated with Co-containing molecular ferroelectric crystals in an island shape;

[0067] The positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ;

[0068] The Co-containing ferroelectric crystal is [(CH 3 ) 3 NCH 2 Cl]CoCl 4 , based on the mass of the core, the mass content of the Co-containing ferroelectric crystal is 2.12wt%;

[0069] The thickness of the Co-rich layer is 5 nm, the mass content of Co atoms in the Co-rich layer is 24.7%, and the material of the Co-rich layer is LiNi 0.8 Co 0.6 Mn 0.1 O 2 -Co 0.5 Cl 3 Solid solution.

[0070] This embodiment also provides a method for preparing the composite positive electrode material, the preparation method comprising the following steps:

[0071] (1) At 20°C, 13.3 mmol of CoCl, accounting for 1 wt% of the positive electrode, was added 3 Add to 20 mL of distilled water and stir until dissolved, then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The powder was stirred at 600 rpm for 2 h using a magnetic stirrer to obtain a uniform suspension, which was then heated and evaporated at 60 °C to obtain CoCl 2 The coated cathode material is then heated to 100°C in an oxygen atmosphere. 3The coated positive electrode material is sintered to obtain a positive electrode material with a surface coated with a Co-containing layer, wherein the outer surface of the Co-containing layer contains unreacted CoCl 3 ;

[0072] The sintering temperature is 600°C and the constant temperature time is 8h.

[0073] (2) At 20°C, 26.5 mmol of trimethylethyl chloride (accounting for 1.87 wt% of the mass of the positive electrode material coated with a Co layer) was added to 20 mL of distilled water and stirred until dissolved. Then, the positive electrode material coated with a Co layer was added and stirred at 600 rpm for 3 h at 50°C for in-situ reaction. After filtration, the in-situ generated [(CH 3 ) 3 NCH 2 Cl]CoCl 4 The positive electrode material is then sintered in an oxygen atmosphere at a sintering temperature of 150° C. for a constant temperature time of 5 hours to obtain the composite positive electrode material.

[0074] Example 3

[0075] This embodiment provides a composite positive electrode material, wherein the composite positive electrode material is a core-shell structure, wherein the core is a positive electrode material, the shell is a Co-rich layer, and the outer surface of the Co-rich layer is coated with Co-containing molecular ferroelectric crystals in an island shape;

[0076] The positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 ;

[0077] The Co-containing ferroelectric crystal is [C 5 H 12 N] 2 Bc 4 , based on the mass of the core, the mass content of the Co-containing ferroelectric crystal is 1.26%;

[0078] The thickness of the Co-rich layer is 5 nm, the mass content of Co atoms in the Co-rich layer is 19.4%, and the material of the Co-rich layer is LiNi 0.8 Co 0.6 Mn 0.1 O 2 -1.5Co 0.5 Br 2 Solid solution.

[0079] This embodiment also provides a method for preparing the composite positive electrode material, the preparation method comprising the following steps:

[0080] (1) At 20°C, 10 mmol of 1 wt% positive electrode CoBr 2 Add to 20 mL of distilled water and stir until dissolved, then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The powder was stirred at 600 rpm for 2 h using a magnetic stirrer to obtain a uniform suspension, which was then heated and evaporated at 80 °C to obtain CoBr 2 The coated cathode material is then heated in an oxygen atmosphere to 2 The coated positive electrode material is sintered to obtain a positive electrode material with a surface coated with a Co-containing layer, wherein the outer surface of the Co-containing layer contains unreacted CoBr 2 ;

[0081] The sintering temperature is 800°C and the constant temperature time is 4h.

[0082] (2) At 20°C, 40 mmol of cyclopentylamine (accounting for 1.56 wt% of the mass of the positive electrode material coated with a Co layer) and 30 mL of hydrobromic acid were added to 20 mL of distilled water and stirred until dissolved. Then, the positive electrode material coated with a Co layer was added and stirred at 600 rpm for 1 h at 70°C using a magnetic stirrer to perform an in-situ reaction. After filtering, the in-situ generated Co-rich layer on the surface [C 5 H 12 N] 2 Bc 4 The positive electrode material is then sintered in an oxygen atmosphere at a temperature of 100° C. for a constant temperature time of 3 hours to obtain the composite positive electrode material.

[0083] Example 4

[0084] The difference between this embodiment and embodiment 1 is that in step (1), CoBr 2 Replace with an equimolar amount of CoCl 2 In step (2), butyl bromide is replaced by an equimolar amount of triethanolamine hydrochloride.

[0085] The rest of the preparation methods and parameters were the same as those in Example 1.

[0086] Example 5

[0087] The difference between this embodiment and embodiment 1 is that the amount of bromobutyltriethylenediethylamine added in step (2) is adjusted so that the mass content of the Co molecular ferroelectric crystals in the composite positive electrode material is 0.05%.

[0088] The rest of the preparation methods and parameters were the same as those in Example 1.

[0089] Example 6

[0090] The difference between this embodiment and embodiment 1 is that the amount of bromobutyltriethylenediethylamine added in step (2) is adjusted so that the mass content of the Co molecular ferroelectric crystals in the composite positive electrode material is 7%.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] Example 7

[0093] The difference between this embodiment and embodiment 1 is that in step (1), CoBr 2 Replace with an equal molar amount of cobalt hydroxide.

[0094] The rest of the preparation methods and parameters were the same as those in Example 1.

[0095] Example 8

[0096] The difference between this embodiment and embodiment 1 is that the CoBr 2 The added amount makes the thickness of the Co-rich layer in the composite positive electrode material 1nm.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Example 9

[0099] The difference between this embodiment and embodiment 1 is that the CoBr 2 The added amount makes the thickness of the Co-rich layer in the composite positive electrode material 15nm.

[0100] The rest of the preparation methods and parameters were the same as those in Example 1.

[0101] Example 10

[0102] The difference between this embodiment and embodiment 1 is that the temperature of the in-situ reaction in step (2) is 40°C.

[0103] The rest of the preparation methods and parameters were the same as those in Example 1.

[0104] Embodiment 11

[0105] The difference between this embodiment and embodiment 1 is that the temperature of the in-situ reaction in step (2) is 80°C.

[0106] The rest of the preparation methods and parameters were the same as those in Example 1.

[0107] Example 12

[0108] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (2) is 80°C.

[0109] The rest of the preparation methods and parameters were the same as those in Example 1.

[0110] Embodiment 13

[0111] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (2) is 500°C.

[0112] The rest of the preparation methods and parameters were the same as those in Example 1.

[0113] Comparative Example 1

[0114] The difference between this comparative example and Example 1 is that no CoBr is added in step (1). 2 In step (2), butyl triethylene diethyl amine is not added, that is, the positive electrode material is not coated with a Co-rich layer and a molecular ferroelectric.

[0115] The rest of the preparation methods and parameters were the same as those in Example 1.

[0116] Comparative Example 2

[0117] The difference between this comparative example and Example 1 is that no bromobutyltriethylenediethylamine is added in step (2), that is, no Co-containing molecular ferroelectric crystals are coated in an island-like manner on the surface of the Co-rich layer.

[0118] The rest of the preparation methods and parameters were the same as those in Example 1.

[0119] Comparative Example 3

[0120] This comparative example provides a method for preparing a composite positive electrode material, the preparation method comprising the following steps:

[0121] At 20 ° C, 10 mmol of 1 wt% positive electrode CoBr 2 Add to 20 mL of distilled water and stir until dissolved, then add 20 mmol of bromobutyltriethylenediethylamine ([CH 3 (CH 2 ) 3 -Dabco] + ·Br - ), and finally add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The powder is stirred at 60° C. and 600 rpm for 2 h using a magnetic stirrer, and the product to be sintered is obtained after filtration, and then the positive electrode material is sintered at 300° C. for 4 h to obtain the composite positive electrode material.

[0122] Performance Testing

[0123] The composite positive electrode materials prepared in the above examples and comparative examples were mixed with Li 6 PS 5 Cl sulfide electrolyte and lithium indium alloy negative electrode were assembled into mold batteries, and the battery performance was tested.

[0124] The assembly steps of the mold battery include:

[0125] i. The composite cathode material in each of the above embodiments and comparative examples was weighed and mixed with a sulfide solid electrolyte and a conductive agent and ground to prepare a composite cathode, wherein the mass ratio of the composite cathode material, the electrolyte and the conductive agent was 7:2.5:0.5, and the grinding time was 10 min.

[0126] ii. Weigh 80 mg of Li 6 PS 5 The Cl sulfide electrolyte is added to the solid-state battery mold and pressed into a disc. Then 10 mg of the composite positive electrode is weighed and evenly dispersed on one side of the solid electrolyte disc and pressurized. Then a lithium-indium alloy negative electrode disc is placed on the other side of the solid electrolyte disc. Finally, the mold battery is pressurized and sealed.

[0127] Figure 2 The present invention shows that the island-shaped coating of Li + The mechanism diagram of the transmission channel shows that the present invention utilizes the built-in electric field of the space charge layer to induce the molecular ferroelectric to generate reverse polarons. The distribution of positive and negative charges in the reverse polarons will cause the Li + Redistribution; Due to the Coulomb interaction of like charges repelling each other, the Li + will be redistributed to the negative charge end of the polaron, i.e. Li + The depletion region, corresponding to the polaron in the space charge layer, will be filled with Li ions, forming a Li ion network near the molecular ferroelectric. + The fast transmission channel improves the coulombic efficiency and rate performance of the battery.

[0128] The mold battery was subjected to charge and discharge cycle tests with a voltage range of 2.0-3.7V and a test rate of 0.5C; rate performance tests were performed at rates of 0.1C, 0.2C, 0.5C, 1C and 0.1C in sequence.

[0129] The above test results are shown in Table 1.

[0130] Table 1

[0131]

[0132] analyze:

[0133] As can be seen from the above table, the present invention utilizes Co-containing molecular ferroelectric crystals to perform non-uniform island coating on the Co-rich layer on the surface of the positive electrode material. On the one hand, the charge transfer impedance caused by the space charge layer is suppressed by means of the Co-containing molecular ferroelectric crystals, thereby improving the transmission efficiency of Li ions at the interface between the positive electrode and the electrolyte in the solid-state battery, thereby improving the coulombic efficiency and rate performance of the battery. On the other hand, the Co-rich layer on the surface of the positive electrode material can stabilize the positive electrode electrolyte interface, eliminate the negative effects caused by the interfacial side reactions, element dissolution, contact failure and positive electrode cracks at the positive electrode electrolyte interface, and improve the cycle performance of the battery.

[0134] It can be seen from Example 1 and Example 4 that if butyl triethylene diethylamine is replaced with an equimolar amount of triethanolamine hydrochloride in step (2), the acidic solution environment formed will cause a certain degree of corrosion and damage to the positive electrode, affecting the capacity of the positive electrode.

[0135] It can be seen from Example 1 and Examples 5-6 that if the mass content of the Co-containing molecular ferroelectric crystal is too little, it is not conducive to constructing a Li ion fast transmission channel in the space charge layer, and the rate performance is poor; if the mass content of the Co-containing molecular ferroelectric crystal is too high, it is not conducive to the Li ion transmission at the positive electrode electrolyte interface, the molecular ferroelectric coating layer forms a physical barrier, the impedance is too large, and the Li ion transmission is hindered, and the positive electrode rate performance and capacity are poor.

[0136] It can be seen from Examples 1 and 7 that if CoBr 2 When replaced with an equal mass of cobalt hydroxide, only a thicker Co 3 O 4 The coating layer and molecular ferroelectrics cannot be synthesized, the interface transfer impedance is too large, and the rate performance and capacity are poor.

[0137] It can be seen from Example 1 and Examples 8-9 that if the thickness of the Co-rich layer is too small, an effective positive electrode electrolyte stable interface cannot be formed, the interface side reaction is serious, and the positive electrode cycle stability is poor; if the thickness of the Co-rich layer is too large, the transmission of Li ions at the positive electrode electrolyte interface is affected, the charge transfer impedance is too large, and the positive electrode rate performance and capacity are poor.

[0138] It can be seen from Example 1 and Examples 10-11 that if the temperature of the in-situ reaction is too low, the molecular ferroelectric cannot be effectively synthesized and the positive electrode rate performance is poor; if the temperature of the in-situ reaction is too high, the molecular iron battery is not synthesized purely, resulting in excessive impedance at the positive electrode interface, poor positive electrode rate performance and capacity.

[0139] It can be seen from Example 1 and Examples 12-13 that if the sintering temperature in step (2) is too low, the bonding strength between the synthesized molecular ferroelectric and the positive electrode is poor, and the molecular ferroelectric falls off from the positive electrode due to stress accumulation during the subsequent battery positive electrode cycle process, resulting in poor cycle stability; if the sintering temperature in step (2) is too high, the molecular ferroelectric is destroyed and thermally decomposed, and the reaction products cause a large impedance, affecting the positive electrode capacity.

[0140] It can be seen from Example 1 and Comparative Examples 1-3 that Example 1 and Comparative Example 2 coated with a Co-rich layer show better cycle stability and coulomb efficiency than Comparative Example 1 and Comparative Example 3 without a Co-rich layer, indicating that the Co-rich layer effectively suppresses the side reaction at the positive electrode and electrolyte interface; Example 1 and Comparative Example 3 coated with Co-containing molecular ferroelectric crystals show better rate performance than Comparative Example 1 without a Co-containing molecular ferroelectric crystal coating, indicating that the molecular ferroelectric effectively constructs a Li ion transmission path in the space charge layer at the positive electrode electrolyte interface, improving the transmission kinetics of Li ions. Therefore, Example 1 combines the advantages of the Co-rich layer and the Co-containing molecular ferroelectric crystal in cycle stability and rate performance, respectively, to achieve long-cycle high-rate performance of the positive electrode material.

[0141] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite positive electrode material, characterized in that: The composite positive electrode material is a core-shell structure, the core is the positive electrode material, the shell is a Co-rich layer, and the outer surface of the Co-rich layer is coated with Co-containing molecular ferroelectric crystals in an island shape; The positive electrode material is a ternary positive electrode material, and the general chemical formula is Li(Ni x Co y Mn z )O2, where, x+y+z=1, 0<x<1, 0<y<1, 0<z<1; Based on the mass of the core, the mass content of the Co-containing ferroelectric crystal is 0.1-5%; The preparation method of the composite positive electrode material comprises the following steps: (1) mixing a positive electrode material and a Co-containing halide for liquid phase coating, and then sintering to obtain a positive electrode material with a Co-containing layer coated on the surface; (2) mixing the positive electrode material coated with the Co layer and the N-containing organic matter, performing an in-situ reaction, and sintering after the reaction to obtain the composite positive electrode material; The N-containing organic matter in step (2) includes N-containing heterocyclic organic matter and / or trimethylethylchloroamine.

2. The composite positive electrode material according to claim 1, characterized in that The Co-containing molecular ferroelectric crystal is a Co-containing organic-inorganic hybrid molecular ferroelectric.

3. The composite positive electrode material according to claim 2, characterized in that: The Co-containing organic-inorganic hybrid molecular ferroelectric comprises C 10 N2H 21 CoBr3、C 10 N2H 21 CoCl3、C 10 N2H 21 CoI3, [C5H 12 N]2CoBr4, [C5H 12 N]2CoCl4, [C5H 12 N]2CoI4, [(CH3)3NCH2Cl]CoCl4, [(CH3)3NCH2Br]CoBr4 or [(CH3)3NCH2I]CoI4, or a combination of at least two thereof.

4. The composite positive electrode material according to claim 1, characterized in that The thickness of the Co-rich layer is 1-10 nm; And / or, in the Co-rich layer, the mass content of Co element is ≥15%.

5. A method for preparing a composite positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a positive electrode material and a Co-containing halide for liquid phase coating, and then sintering to obtain a positive electrode material with a Co-containing layer coated on the surface; (2) The positive electrode material coated with the Co layer and the N-containing organic matter are mixed to carry out an in-situ reaction, and then sintered after the reaction is completed to obtain the composite positive electrode material.

6. The preparation method according to claim 5, characterized in that: The Co-containing halide in step (1) includes a divalent Co-containing halide and / or a trivalent Co-containing halide.

7. The preparation method according to claim 6, characterized in that: The divalent Co-containing halide includes any one or a combination of at least two of CoF2, CoCl2, CoBr2 or CoI2; and / or, the trivalent Co-containing halide comprises CoF3 and / or CoCl3; And / or, the mass of the Co-containing halide accounts for 0.5-1.5wt% of the mass of the positive electrode material.

8. The preparation method according to claim 5, characterized in that: The sintering temperature in step (1) is 600-800°C and the constant temperature time is 4-8h; And / or, the sintering treatment in step (1) is carried out in an oxygen atmosphere.

9. The preparation method according to claim 5, characterized in that: The N-containing organic matter in step (2) has a spherical or spherical structure; And / or, the N-containing organic matter in step (2) includes N-containing heterocyclic organic matter and / or trimethylethylchloroamine.

10. The preparation method according to claim 9, characterized in that: The N-containing heterocyclic organic compound includes a five-membered N-containing heterocyclic organic compound and / or a six-membered N-containing heterocyclic organic compound; And / or, the N-containing heterocyclic organic compound includes bromobutyltriethylenediethylamine; And / or, the mass of the N-containing organic matter in step (2) accounts for 0.2-2.5wt% of the mass of the positive electrode material coated with the Co-containing layer on the surface.

11. The preparation method according to claim 5, characterized in that: The temperature of the in-situ reaction in step (2) is 50-70°C, and the constant temperature time is 1-3h; And / or, the sintering temperature in step (2) is 100-300° C. and the constant temperature time is 3-5 h; And / or, the sintering in step (2) is carried out in an oxygen atmosphere.

12. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: (1) A Co-containing halide and a solvent are stirred and mixed, and then a positive electrode material is added and stirred for 1-3 hours to obtain a suspension, and then dried at a temperature of 60-100° C. to obtain a positive electrode material coated with a Co-containing halide, and then the Co-containing halide-coated positive electrode material is sintered in an oxygen atmosphere to obtain a positive electrode material with a surface coated with a Co-containing layer, wherein the outer surface of the Co-containing layer contains unreacted Co-containing halide; The sintering temperature is 600-800°C and the constant temperature time is 4-8h. (2) Stirring and mixing the N-containing organic matter and the solvent, and then adding the positive electrode material with the surface coated with the Co layer, and performing an in-situ reaction at a temperature of 50-70°C for 1-3 hours to obtain a positive electrode material with a Co-rich layer surface in-situ generated with Co molecular ferroelectrics, and then sintering in an oxygen atmosphere at a temperature of 100-300°C and a constant temperature time of 3-5 hours to obtain the composite positive electrode material.

13. A solid-state battery, characterized in that: The positive electrode plate of the solid-state battery includes the composite positive electrode material as described in any one of claims 1 to 4, or includes the composite positive electrode material prepared by the preparation method as described in any one of claims 5 to 12.

Citation Information

Patent Citations

  • Cobalt-containing organic-inorganic hybrid molecular ferroelectric material and preparation method thereof

    CN114014894A

  • Ultrahigh-nickel polycrystalline positive electrode material as well as preparation method and application thereof

    CN118841558A